Antibacterial Albumin-Tannic Acid Coatings for Scaffold-Guided Breast Reconstruction - Cometta, Silvia; Bock, Nathalie; Suresh, Sinduja; Dargaville, Tim R.; Hutmacher, Dietmar W. (Frontiers in Bioengineering and Biotechnology, 2021)
Infection is the major cause of morbidity after breast implant surgery. Biodegradable medical-grade polycaprolactone (mPCL) scaffolds designed and rooted in evidence-based research offer a promising alternative to overcome the limitations of routinely used silicone implants for breast reconstruction. Nevertheless, as with any implant, biodegradable scaffolds are susceptible to bacterial infection, too. Especially as bacteria can rapidly colonize the biomaterial surface and form biofilms. Biofilm-related infections are notoriously challenging to treat and can lead to chronic infection and persisting inflammation of surrounding tissue. To date, no clinical solution that allows to efficiently prevent bacterial infection while promoting correct implant integration, has been developed. In this study, we demonstrated to our knowledge for the first time that the physical immobilization of 1% and 5% human serum albumin (HSA) onto the surface of 3D printed macro- and microporous mPCL scaffolds, resulted in a reduction of S. aureus colonization by 71.7± 13.6% and 54.3± 12.8%, respectively. Notably, when treatment of scaffolds with HSA was followed by tannic acid (TA) crosslinking/stabilization, uniform and stable coatings with improved antibacterial activity were obtained. The HSA/TA-coated scaffolds were shown stable when incubated at physiological conditions in cell culture media for 7 days. Moreover, they were capable of inhibiting the growth of S. aureus and P. aeruginosa, two of the most commonly found bacteria in breast implant infections. Most importantly, 1%HSA/ 10%TA- and 5%HSA/ 1%TA-coated scaffolds were able to reduce S. aureus colonization on the mPCL surface, by 99.8± 0.1% and 98.8± 0.6%, respectively, in comparison to the non-coated control specimens. This system offers a new biomaterial strategy to translate effectively the prevention of biofilm-related infections on implant surfaces without relying on the use of prophylactic antibiotic treatment.